Effect of Supply Chain Management on Export comparative Advantages of Russia and Post-Soviet Countries - Kirill Andreevich Ermolaev; Shohruh Esanovich Yormatov (International Journal of Supply Chain Management, 2020)
Abstract— The purpose of this paper is a comparative analysis of supply chain management in Russian and post-soviet countries export. The index of revealed comparative advantage (RCA) calculated for ten countries in seven aggregated product categories for the period 2012–2018. Additionally, the dynamics of trade complementarity index (TCI) between Russia and other chosen countries were analyzed. The RCA index analysis outcome of the main export categories of goods in supply chain allows us to conclude about Russian significant comparative advantage in fuel and metals export comparatively with post-Soviet countries. Dynamics of the RCA index show insignificant structural changes for the export profile of supply chain management. In turn, analyzed dynamics of TCI allow conclude increasing of trade complementarity between Russian and trading partners. Higher TCI index values for not a member of the Eurasian Economic Union countries suggest that, under certain conditions, trade flows between Russia and these post-Soviet countries may significantly increase by using supply chain system. The obtained results contribute to the informational and analytical base for further researches on effectiveness of the supply chain management in export mechanism development of post-Soviet countries and increasing their competitiveness in the global market.